Peran Guru Kelas Untuk Meningkatkan Kepercayaan Diri Siswa Terhadap Penyandang Disabilitas Di Sekolah Dasar Luar Biasa Inpres 73 Malaingkedi Kota Sorong - Nisa Juniar Anggraini; Isra Oktaviani (MISOOL: Jurnal Pendidikan Dasar, 2023)
This Special Elementary School in the city of Sorong educates its students based on the school curriculum structure (SDLB) but adapts it to the needs of children with special needs at the school. Changes in physical conditions also affect a child's sense of self-confidence, and physical or mental disabilities can cause a person to feel inferior and even embarrassed to interact with other people. This is interesting to research because this research focuses on the role of class teachers in increasing the self-confidence of people with disabilities. This research uses qualitative research in the form of actions and words from samples that were observed or interviewed directly, namely the principal, class teachers and students of the Inpres 73 Extraordinary Elementary School in Malaingkedi, Sorong City. There are various ways to increase the self-confidence of students with disabilities, things that must be instilled in students are that they must have the courage to try new positive things and always practice worship and get closer to God. This can teach students to always be grateful. about the situation they have